2017
DOI: 10.21037/jgo.2017.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and toxicity of FOLFIRINOX and gemcitabine with nab-paclitaxel in unresectable pancreatic cancer

Abstract: Background: Irinotecan, oxaliplatin and leucovorin-modulated fluorouracil (FOLFIRINOX) and the combination regimen of gemcitabine and nanoparticle albumin-bound paclitaxel (GnP) (nab-PTX) improve the prognosis of patients with metastatic pancreatic cancer. However, no study has compared the efficacy of the two regimens. We compared retrospectively the efficacy and safety of the two regimens in patients with unresectable pancreatic cancer. Methods: Thirty-eight patients with unresectable locally advanced or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 9 publications
1
70
0
3
Order By: Relevance
“…Gemcitabine-based combination regimens, with either S-1 or nab-paclitaxel, have been associated with more frequent chemotherapy-related AEs [ 15 , 16 ]. Previous clinical trials support the conclusion that FOLFIRINOX is more toxic than gemcitabine and nab-paclitaxel [ 17 ]. In Asia, most patients with APC cannot tolerate the AEs associated with FOLFIRINOX; therefore, its application is limited.…”
Section: Discussionmentioning
confidence: 89%
“…Gemcitabine-based combination regimens, with either S-1 or nab-paclitaxel, have been associated with more frequent chemotherapy-related AEs [ 15 , 16 ]. Previous clinical trials support the conclusion that FOLFIRINOX is more toxic than gemcitabine and nab-paclitaxel [ 17 ]. In Asia, most patients with APC cannot tolerate the AEs associated with FOLFIRINOX; therefore, its application is limited.…”
Section: Discussionmentioning
confidence: 89%
“…In this manner, while the therapeutic effect of CS on patients with UR-PC is investigated, progress of chemo(radio)therapy is remarkable, and FOLFIRINOX or GnP regimen is used as first-line chemotherapy for patients with UR-PC. 12,13,[24][25][26] Hackert et al 13 reported that patients with UR-PC who received FOLFIRINOX as NST had a higher conversion rate and a better prognosis than those received other regimen and they advocated that FOLFIRINOX should be first-line therapy for patients with UR-PC. As the antitumor effect of these regimens are very high, candidates for CS are expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…FOLFOX itself is also a promising candidate for further drug combination, as it has been combined with the chemotherapy irinotecan to form FOLFIRINOX, the first-line treatment for both adjuvant chemotherapy and metastatic PDAC (9,10). This combination's greatly increased efficacy was a breakthrough in PDAC, but the addition of the cytotoxic irinotecan leads to increased frequency and severity of side effects (9)(10)(11). Therefore, at many centers, it is currently only recommended to healthier, younger patients, which may exclude as many as 75% of metastatic PDAC patients (12).…”
Section: Introductionmentioning
confidence: 99%